2010
DOI: 10.1093/glycob/cwq045
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of UDP-glucose pyrophosphorylase reveals a UDP-glucose independent UDP-galactose salvage pathway in Leishmania major

Abstract: The nucleotide sugar UDP-galactose (UDP-Gal) is essential for the biosynthesis of several abundant glycoconjugates forming the surface glycocalyx of the protozoan parasite Leishmania major. Current data suggest that UDP-Gal could arise de novo by epimerization of UDP-glucose (UDP-Glc) or by a salvage pathway involving phosphorylation of Gal and the action of UDP-glucose:alpha-D-galactose-1-phosphate uridylyltransferase as described by Leloir. Since both pathways require UDP-Glc, inactivation of the UDP-glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 55 publications
2
24
0
1
Order By: Relevance
“…In L. major both pathways are active and contribute to the UDP-Gal synthesis [14,15]. In contrast, the T. brucei genome lacks a homologue of the USP gene and it has a pseudogene of GALK [12].…”
Section: Introductionmentioning
confidence: 99%
“…In L. major both pathways are active and contribute to the UDP-Gal synthesis [14,15]. In contrast, the T. brucei genome lacks a homologue of the USP gene and it has a pseudogene of GALK [12].…”
Section: Introductionmentioning
confidence: 99%
“…Galactose is likely to be converted into Gal-1-P by the putative galactokinase present in the genome of Leishmania major (LmjF35.2740) and subsequently activated into UDP-Gal by an unusual UDP-sugar pyrophosphorylase (USP; EC 2.7.7.64) recently identified in L. major as well as in T. cruzi. [17][18][19] Like plant USPs, the leishmanial enzyme exhibits broad in vitro specificity but preferentially activates Gal-1-P and Glc-1-P. 17,[20][21][22] In L. major, deletion of UGP leads to a mild phenotype associated with residual UGP activity likely due to USP. 19 Similarly, USP seems to partially compensate for deficiency of UGPs in plants.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Like plant USPs, the leishmanial enzyme exhibits broad in vitro specificity but preferentially activates Gal-1-P and Glc-1-P. 17,[20][21][22] In L. major, deletion of UGP leads to a mild phenotype associated with residual UGP activity likely due to USP. 19 Similarly, USP seems to partially compensate for deficiency of UGPs in plants. 23,24 In vivo, it likely plays a role in the salvage of several monosaccharides and is essential for pollen development.…”
Section: Introductionmentioning
confidence: 99%
“…(Paściak et al, 2010b) Aspergillus fumigatus Glycoinositolphospho-ceramides TOF The mitA gene shown to be required for mannosylation (Kotz et al, 2010) Hymenobacter sp. Carotenoids MALDI Identification of 2'-methyl and 1'-xylosyl derivatives of 2'hydroxyflexixanthin (Klassen et al, 2009) Leishmania major Glycoinositolphospholipids TOF (CHCA), ESI-MS n Demonstration of a UDPglucose independent UDPgalactose salvage pathway (Lamerz et al, 2010)…”
Section: A Cancermentioning
confidence: 99%